Has the COVID-19 lockdown wreaked havoc on diet and lifestyle choices? - S., Manjula; U., Sharath (International Journal Of Community Medicine And Public Health, 2022)
Background: The COVID-19 pandemic induced nationwide lockdown affected the 1.3 billion population of India. Home confinement and isolation have caused sudden lifestyle and dietary changes. A healthy diet is crucial in this period. Studies have shown that subjects with severe obesity and smokers are at higher risk of COVID-19. Such studies can help advocate nutritional interventions to support the health status of people. Hence this study aims to investigate the impacts of COVID-19 lockdowns on dietary behavior and lifestyle habits of adults. Methods: This is a cross sectional study done in Chengalpattu district with a sample size of 150 adults. Two-stage random sampling was done and a semi structured, self-administered online questionnaire was used. IBM statistical package for the social sciences (SPSS) v.21 was used for analyses. Results: In this study 46% people reported snacking more during the COVID-19 lockdown. An increase in alcohol consumption was seen in 14.6% and 45% smokers experienced a rise in smoking frequency. There was a 2.6% decrease in the number of people spending time for physical fitness during lockdown and the perception of weight gain was observed in 46.7% of respondents. Sleep duration seemed to have improved in the lockdown with 64.7% people sleeping for 7-9 hours during lockdown, compared to only 40.7% people before lockdown. Conclusions: The current study found that there was a negative impact of lockdown on the dietary habits and lifestyle choices of the people. Hence it is important to advocate appropriate nutritional interventions and create awareness among people about healthy diet and lifestyle choices during these the COVID-19 pandemic.